Adab Mencari Ilmu dalam Perspektif Al-Qur'an dan Hadis: Analisis Nilai-nilai Akhlak dalam Membentuk Karakter Penuntut Ilmu - Helsa Malika Alea Casta; Nur Afiya Kamila; Ririn Shafitri; Muhammad Yahya (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
The way of asking for knowledge, as shown in the Qur'an and Hadith, is very important for helping students develop good morals. In Islam, learning is not just about gaining information, but also about growing into a person with good values and behaving in a moral way. This research looks into the idea of proper behavior when seeking knowledge, as shown in the Qur'an and Hadith, and how it helps shape a person's character. This study uses a qualitative method, focusing on library research, and looks at interpretations of the Qur'an, Hadith sources, books, and scientific articles about Islamic education and ethics. The results show that being sincere, humble, patient, respectful towards teachers, and using what you learn are the main values that should go along with learning. Combining knowledge with good manners can help form people who are both smart and have strong values. So, teaching proper manners in schools should still be a top focus to raise people who have good values and useful knowledge.